2018
DOI: 10.1039/c8cc04258f
|View full text |Cite
|
Sign up to set email alerts
|

Target discovery of ebselen with a biotinylated probe

Abstract: Despite numerous studies on ebselen over the past decade, its cellular targets remain obscure. Here we synthesized a biotinylated ebselen probe (biotin-ebselen) and characterized ebselen-binding proteins via an efficient activity-based protein profiling (ABPP) method, which allowed for the robust identification of 462 targeted proteins in HeLa cells. This first work of global target profiling of ebselen will be helpful to re-design ebselen-based therapy appropriately in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…When Cys6 is present, however, a population of SOD1 molecules appear receptive to ligand binding within the β-barrel. This highlights the promiscuity of ebselen; an assessment of stable ebselen binding within cells indicated over 400 protein targets [86]. Furthermore, the selenylsulphide bond is prone to cleavage by cytoplasmic reductants unless it is protected.…”
Section: Ebselenmentioning
confidence: 99%
See 1 more Smart Citation
“…When Cys6 is present, however, a population of SOD1 molecules appear receptive to ligand binding within the β-barrel. This highlights the promiscuity of ebselen; an assessment of stable ebselen binding within cells indicated over 400 protein targets [86]. Furthermore, the selenylsulphide bond is prone to cleavage by cytoplasmic reductants unless it is protected.…”
Section: Ebselenmentioning
confidence: 99%
“…Furthermore, the selenylsulphide bond is prone to cleavage by cytoplasmic reductants unless it is protected. As a consequence stable cytoplasmic binding to SOD1 Cys111 has not been observed [84,86]. However, ebselen is a thiol oxidase and was able to catalyse formation of the SOD1 intra-subunit disulphide bond within cells in the absence of overexpressed hCCS [84].…”
Section: Ebselenmentioning
confidence: 99%
“…The recent introduction of drug-derivatized xylosides is a development of this idea. Ebselen is a small molecule seleno-compound that interacts with several enzymes some of which are involved in GAG biosynthesis and is cytotoxic at elevated concentrations [74,88]. In a proof-of-concept study, the cytotoxicity in cancer cells of Ebselen-β-D-xyloside was found to exceed that of Ebselen alone.…”
Section: Gag Metabolic Enzymes As Targetmentioning
confidence: 99%
“…Considering the great demand for a simple and efficient method for both off‐ and on‐DNA C−H selenylation, and in continuation of our research program in DELs, we were interested in developing a new and versatile selenide reagent, and especially one that would allow introduction of multiple functional groups for diversification beyond selenylation. We envisaged that benzoselenazolone could meet these demands in that the N−Se bond is polarized and can be cleaved via nucleophilic attack by sulfhydryl and Grignard reagents . Moreover, the nucleophilic character of C(sp 2 )−Rh III species suggested a good probability of success .…”
Section: Introductionmentioning
confidence: 99%